Marseille, Montpellier und das Mittelmeer. Die Entstehung des südfranzösischen Fernhandels im 12. und 13. Jahrhundert - Nicolussi-Koehler, Stephan (Pariser Historische Studien, 2021)
The book examines how the integration of local merchants in the south of France contributed to the commercial expansion of the cities of Marseille and Montpellier in the 12th and 13th centuries. The origin of the flourishing long-distance trade is not sought in the establishment of the Crusader states in the East, but instead is explored at its roots, the local trade cycles in the hinterland of the port cities. The book is built around micro-historical sketches about specific merchant families, merchant ships and trade privileges, thus revealing unknown connections and new perspectives. Mediterranean trade is described from the perspective of inland merchants, and trade with the Levant is seen from the perspective of Provençal and Catalan merchants who traded through foreign financial centres and under foreign flags. The book explores how the hinterland made the long-distance trade of Marseille and Montpellier possible in the first place by providing goods, capital and manpower.